How the Role of Emotional Pleasure Mediates the Value of Shopee Live: Bagaimana Peran Kesenangan Emosional Memediasi Nilai Pada Shopee Live - Revando Rahmad Dian; Astri Yuza Sari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study examines the role of emotional pleasure in mediating the effects of hedonic and utilitarian values on purchase intention in Shopee Live. Despite the platform's unique features, such as interactive live shopping experiences, purchase intentions remain lower compared to competitors like TikTok. Using a quantitative approach, data were collected from 150 respondents familiar with Shopee Live through an online questionnaire. The data were analyzed using SmartPLS software to test hypotheses. The findings reveal that hedonic value significantly influences emotional pleasure and purchase intention, while utilitarian value significantly impacts purchase intention but not emotional pleasure. Moreover, emotional pleasure does not significantly mediate the relationship between hedonic and utilitarian values and purchase intention. These results highlight the importance of hedonic experiences in driving purchase intentions and suggest that emotional pleasure alone is insufficient to mediate these effects. The study underscores the need for alternative strategies to enhance purchase intentions on live shopping platforms